Preventing child maltreatment: Beneficial side effects of public childcare provision - Malte Sandner; Stephan L. Thomsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
We investigate the impact of childcare provision on cases of child maltreatment. For identification, we exploit a governmental reform introducing mandatory early childcare in Germany that generated large temporal and spatial variation in childcare coverage at the county-level. Using high-quality administrative data covering all reported child maltreatment cases in a county per year, our results show that maltreatment cases decline by 1.8% if a county increases childcare slots by one percentage point. Because child maltreatment leads to enormous societal costs, we provide evidence that the provision of universal public childcare can prevent some of these costs.
Keywords: J13; J12; I38; 330; Child Maltreatment; Child abuse and neglect; Early childcare; Prevention